Schooling and wage income losses due to early-childhood growth faltering in developing countries: national, regional, and global estimates. - Fink,G; Peet,E; Danaei,G; Andrews,K; McCoy,DC; Sudfeld,CR; Smith,Fawzi MC; Ezzati,M; Fawzi,WW (American Journal of Clinical Nutrition, 2016)
BACKGROUND: The growth of >300 million children <5 y old was mildly, moderately, or severely stunted worldwide in 2010. However, national estimates of the human capital and financial losses due to growth faltering in early childhood are not available. OBJECTIVE: We quantified the economic cost of growth faltering in developing countries. DESIGN: We combined the most recent country-level estimates of linear growth delays from the Nutrition Impact Model Study with estimates of returns to education in developing countries to estimate the impact of early-life growth faltering on educational attainment and future incomes. Primary outcomes were total years of educational attainment lost as well as the net present value of future wage earnings lost per child and birth cohort due to growth faltering in 137 developing countries. Bootstrapped standard errors were computed to account for uncertainty in modeling inputs. RESULTS: Our estimates suggest that early-life growth faltering in developing countries caused a total loss of 69.4 million y of educational attainment (95% CI: 41.7 million, 92.6 million y) per birth cohort. Educational attainment losses were largest in South Asia (27.6 million y; 95% CI: 20.0 million, 35.8 million y) as well as in Eastern (10.3 million y; 95% CI: 7.2 million, 12.9 million y) and Western sub-Saharan Africa (8.8 million y; 95% CI: 6.4 million, 11.5 million y). Globally, growth faltering in developing countries caused a total economic cost of $176.8 billion (95% CI: $100.9 billion, $262.6 billion)/birth cohort at nominal exchange rates, and $616.5 billion (95% CI: $365.3 billion, $898.9 billion) at purchasing power parity-adjusted exchange rates. At the regional level, economic costs were largest in South Asia ($46.6 billion; 95% CI: $33.3 billion, $61.1 billion), followed by Latin America ($44.7 billion; 95% CI: $19.2 billion, $74.6 billion) and sub-Saharan Africa ($34.2 billion; 95% CI: $24.4 billion, $45.3 billion). CONCLUSIONS: Our resu